2005
DOI: 10.1111/j.0300-9475.2005.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry of the B‐Cell Component in Lower Lip Salivary Glands of Sjögren's Syndrome and Healthy Subjects

Abstract: Serial sections of lower lip salivary gland (LSG) biopsies were examined by immunohistochemistry, using a battery of B- and partly T-related antibodies (CD5, CD20, CD21, CD27, CD38, CD45RO, CD79a, Bcl-2 and Bcl-6) in different groups of subjects: healthy controls and clinically verified smoking or nonsmoking cases of primary Sjögren's syndrome (SS). The purpose was to characterize the B-cell pattern of the lymphocytic foci and of the tiny perivascular infiltrates preceding the development of foci. Hyperplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 55 publications
0
17
0
4
Order By: Relevance
“…There are reports where CD38 expression is increased in B and T cells from patients with LES and rheumatoid arthritis . In addition, it has been reported an increase in CD38 + CD138 + plasma cells and others subpopulations CD38 + cells from peripheral blood and lower lip salivary gland (LSG) of Sjögren′s syndrome patients (SS) . Such reports suggest that CD38 may contribute to the pathogenesis of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports where CD38 expression is increased in B and T cells from patients with LES and rheumatoid arthritis . In addition, it has been reported an increase in CD38 + CD138 + plasma cells and others subpopulations CD38 + cells from peripheral blood and lower lip salivary gland (LSG) of Sjögren′s syndrome patients (SS) . Such reports suggest that CD38 may contribute to the pathogenesis of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated the presence of a more mature subset of transitional B-cells, termed T2 B-cells, which were CD19+IgD+CD38ÀIgM+CD21+CD23+ and present within pSS salivary glands [22,24]. However, another study on lower lip salivary gland (LSG) biopsies reported that in contrast to the widely dispersed presence of B-cells expressing CD38+, CD79a+ and CD5+ to a minor degree, and lacking CD20, CD21 and CD27 in LSGs from healthy controls, LSGs from pSS patients showed CD20+ B-cells and CD27+/CD38+ B-cells, with the CD20+ B-cells being concentrated in perivascular regions that did not overlap with focal infiltrates filled with the CD27+/CD38+ B-cell subset [25]. A more recent study also detected significant numbers of CD138+, non-proliferating, Bcl-2 expressing plasma cells in the salivary glands of pSS patients with high focus scores [26].…”
Section: In Salivary Glandsmentioning
confidence: 99%
“…IgD -CD38 ++ CD27 [54], which is a marker for memory B cells but is also seen in PC, in addition to genuine memory B cells, i.e., IgM-only cells with IgV gene somatic mutations [55], have been identified in the SG infiltrates. This accumulation could be caused by the ectopic expression of B cell chemokines, such as CXCL13, within the GC [56], combined with that of the CXCR5 receptor on B lymphocytes [57].…”
Section: Plasma Cellmentioning
confidence: 99%